Edukasi Kesehatan Gigi Berbasis Individual terhadap Keterampilan Menyikat Gigi pada Anak Disabilitas Intelektual Ringan - Sabilillah, Muhammad Fiqih; Daniati, Nia (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2025)
Oral and dental health is a vital aspect of general health that must be addressed early, including for children with mild intellectual disabilities. These children face limitations in understanding information, responding to instructions, and controlling fine motor skills, which reduces their ability to maintain personal hygiene, particularly in brushing their teeth independently and properly. One strategy to improve toothbrushing skills in this group is through individualized oral health education tailored to each child’s comprehension and ability. This study aimed to examine the effect of individualized oral health education on toothbrushing skills in children with mild intellectual disabilities. The research used a quasi-experimental design with a pretest-posttest control group approach. Respondents were selected using a simple random sampling technique among children with mild intellectual disabilities attending Special Needs Schools, with 20 children in each group. The study included two groups: the intervention group, which received individualized education, and the control group, which did not receive similar treatment. A structured checklist was used to assess toothbrushing skills before and after the 21 day intervention. The results showed a significant improvement in the intervention group’s toothbrushing skills, from a pre-intervention mean score of 7.34 ± 1.440 to a post-intervention score of 15.81 ± 1.421 (p < 0.001). Meanwhile, the control group showed no significant change (p = 0.505). The difference in skill improvement between the groups was also statistically significant (p < 0.001). In conclusion, individualized oral health education is proven effective in enhancing toothbrushing skills among children with mild intellectual disabilities.